Communicating the Value of Ergonomics to Management – Part 2: Ergonomics ROI Case Study Applications. (September 2017) - Reid, Christopher R.; Johnson, Peter W.; Marklin, Richard W.; Seeley, Patricia; Spielholz, Peregrin; Goggins, Rick
More than ever, human factors engineers and ergonomists need to justify our practice's value to management. How can we effectively communicate with management? How should we present a Return on Investment (ROI) that leadership will find useful that addresses company profits, cost savings, productivity, first time quality, and turnover? What else does management care about other than ROI? This second panel in a two panel series will specifically highlight case studies in which presenters give examples of situations in which ROI for ergonomics was investigated from a business value. The session will start with four case study lectures followed by a panel discussion led by the moderators. The audience will be encouraged to participate with their own questions and comments.